Value Chain Analysis of Maize in Mahabubnagar District of Telangana State, India - Raja Krishna Murthy, Morla (British Journal of Marketing Studies, 2016)
India is the sixth largest producer of maize in the world, and contributed about 2 per cent to the global maize production of 855.72 million tonnes (Mt) in 2012-13. Karnataka and Andhra Pradesh are the corn belts from South where Karnataka alone occupies 12% of the total area (one million ha) and contributes nearly 16% of its total production. Nearly ¾ of the produce is being processed as animal feed and remaining for human consumption and industrial use. There is a huge demand for maize and maize products because, it is rich in lysine, tryptophan, amino acids and low fat content and it is a good product for diabetic and obese disorders. Now a days there is a more demand for maize value added products in urban and peri-urban areas, indicating a vast scope for fortification as nutritional supplementation at all the stages right from farmer’s field to consumer’s plate. The rich nutri-maize is available in abundance to the consumers at relatively cheaper price (compared to other cereals) can be further commercially exploited for nutritive health foods by value addition and making available them at affordable price for the advantage of vulnerable groups and other consumers at large. The main objective of the study was to carry out value chain analysis of maize in Mahabubnagar district and environs with a view to identify potential production, demand and supply, value chain, value additions, key sector constraints and opportunities and appropriate interventions.